Sejarah Tokoh Balâghah Terkemuka di Dunia Arab dan Islam - Imelda Fedian; Wahidatul Husna; Nursumayyah Damanik (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article aims to recognize and understand the development of the story of Ahmad Al-Hasyimi. Ahmad Al-Hasyimi is one of the important figures in the science of balaghah who has made a major contribution to the development of the Arabic language, especially in the fields of rhetoric and literature. Through his famous work “Jawahir Al-Balaghah”, he succeeded in simplifying Balâghah so that it is easier to understand by Arabic language students and researchers. According to Ahmad Al-Hasyimi, the aim of his Balâghah is to convey meaning with clarity, beauty and attractiveness that can influence the reader or listener. Literature that uses methods by collecting secondary data in the form of journal papers, online articles.